ANALISIS KINERJA KEUANGAN PADA PT.PERKEBUNAN NUSANTARA V PEKANBARU PROVINSI RIAU - Nasution, Fahrezi; Satriana Dewi, Ilma (DINAMIKA PERTANIAN, 2023)
The company's financial performance is the result of many individual decisions made continuously by management to generate profits effectively and efficiently. The purpose of this study is to determine and analyze the financial performance of PT Perkebunan Nusantara V Pekanbaru in terms of liquidity ratio, solvency ratio, activity ratio, profitability ratio for the 2018–2022 period, and vertical comparison analysis for the 2021–2022 period. The method used for the research was a literature study. The research place is PT Perkebunan Nusantara V, which is located on Rambutan Street, Pekanbaru. This research was conducted for six months, starting in January and ending in June 2023. The data used is secondary data. The data analysis used is descriptive, qualitative, and quantitative, with a financial ratio analysis. The results of this study conclude that the liquidity ratio for the current ratio and quick ratio can be said to be not good and that the company has not been able to pay all current liabilities using the current assets owned by the company. While the cash ratio is said to be very good, Based on the solvency ratio, namely debt to total assets and debt to equity ratio, it can be concluded that it is not good and has not been able to pay all of the company's obligations using all of the company's assets and capital. Based on the profitability ratio, it can be concluded that the company's net profit margin and return on assets can be said to be poor and that it has not been able to generate net income. Meanwhile, the gross profit margin and return on equity can be said to be very good. Based on the activity ratio, namely total assets turnover and working capital turnover, it was found that the activity ratio for total assets turnover was not good and was able to manage all company assets consisting of current assets and fixed assets to generate sales, and the activity ratio for working capital turnover was very good. The results of the vertical analysis comparison were carried out in 2021–2022, and the comparison for the company's liquidity level in 2022 was better than the previous year. The solvency level in 2022 decreased compared to the previous year. Based on the profitability of the company, the comparison in 2021–2022 for the company's profitability level was good because the number of percentages reached industry standards.